KEEFEKTIFAN MODEL PEMBELAJARAN KOTEKSTUAL TIPE INKUIRI TERHADAP MENULIS KARANGAN DESKRIPSI SISWA KELAS X SMA NEGERI 3 MAKASSAR - A. Vivit Angreani; Patahuddin Patahuddin (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to examined the learning of writing descriptions text by using the model of learning pictures and pictures of students’ class X in SMA Negeri 3 Makassar and proved the effectiveness of contextual learning model type inquiry in writing description text of students’ class X in SMA Negeri 3 Makassar. The type of this research was a quasi-experimental design. This research used Pretest-Posttest Control Group design, using experimental group and control group. This research was conducted in SMA Negeri 3 Makassar. The population in this study were all students of Class X which were 246 students. Sampling was done by Random Sampling or random grouping. The selected sample was Class X1 as the experiment class that matches 29 students and class X2 as the control class. The collected data was analyzed by using descriptive statistics and inferential statistics. Statistical analysis techniques used are descriptive statistical techniques and inferential analysis (parametric). The results showed that students' ability in experimental class in applying contextual learning model of inquiry type showed very good result. Students able to obtain interval value of 90-100 that is equal to 10,3% or as many as 3 students, interval value of 80-89 that is equal to 69% or as many as 20 students and that there is interval value of 65-79 that is equal to 20,7% or as many as 6 students. Students' ability in control class in writing description text by applying picture and picture model shows inadequate result. Students who achieve and are in the interval value of 80-89 of 10.3% or as many as 3 students and who are at the interval value of 65-79 that is 89.7% or as many as 26 students. Thus, based on the results of these studies, it shows that the use of inquiry-type contextual models is effectively applied in the learning of writing descriptive text. This is shown in the result of hypothesis test using inferential statistics analysis of test type tt independent samples test obtained t-count equal to -6,954 and t-table equal to 2,003 because t-count value> t-table, then null hypothesis (H0) rejected and alternative hypothesis (H1) accepted. This shows that the inquiry model of inquiry type is effectively applied in learning text writing description of students’ class X in SMA Negeri 3 Makassar